Revision of Acrochordonoposthia Reisinger, 1924 (Rhabditophora, Typhloplanidae, Protoplanellinae) with the description of one new species - Houben, Albrecht M.; Proesmans, Willem; Bert, Wim; Artois, Tom J. (Zootaxa, 2014)
An overview of the morphology, taxonomy and distribution of all known species of the rhabdocoel taxon Acrochordonoposthia is provided. One new species A. vandeputae n. sp. is described from Graz (Austria). This new species can easily be distinguished from its congeners by the morphology of its copulatory organ, which contains a straight cirrus lined with spines. All species of Acrochordonoposthia are compared with one another, and an updated identification key is provided.